Computational economics a perspective from computational intelligence - Chen, Shu-Heng 1959-; Jain, Lakhmi C.; Tai, Chung-Ching (Computational intelligence and its applications series, 2006)
"This book identifies the economic as well as financial problems that may be solved efficiently with computational methods and explains why those problems should best be solved with computational methods"--Provided by publisher.